Characterization of the complete chloroplast genome and comparative analysis of the phylogeny and codon usage bias of three Yunnan wild rice species - Li, Rongxin; Wang, Bo; Xiao, Suqin; Chen, Ling; Yin, Fuyou; Li, Jinlu; Jiang, Cong; Zhang, Dunyu; Zhong, Qiaofang; Zhang, Yun; Xing, Jiaxin; Cheng, Zaiquan; et al. (Frontiers in Plant Science, 2025)
BackgroundWild rice species with a rich genetic diversity, wide adaptability, and high photosynthetic rates provide a valuable genetic reservoir for rice breeding.MethodsIn this study, the chloroplast (cp) genomes of three Yunnan wild rice species, namely Oryza rufipogon, Oryza officinalis, and Oryza granulata, were sequenced using second-generation sequencing technology, followed by assembly and annotation. Phylogeny and codon usage bias were analyzed using MEGA and RStudio.ResultsThe total lengths of the cp genomes of the three species ranged from 134,556 to 135,937 bp, with a GC content of 39.0%. The large single-copy region of Oryza granulata was 2000 bp longer than that of the other two species. In total, 133 genes were identified in the cp genome, including domestication genes psbZ, ycf68, and lhba. Phylogenetic analysis showed that Oryza rufipogon is distinct from the Indian Oryza nivara, Oryza officinalis evolved from Oryza australiensis, and Oryza granulata shared a closer relationship with Oryza brachyantha. The average effective number of codons of the three species was above 45, indicating weak codon usage bias.ConclusionAnalysis of the ENC, PR2, and neutrality plots revealed that natural selection played a significant role in the chloroplast codon usage bias of the three species, mainly regulating genes involved in self-replication and photosynthesis. Fourteen optimal codons were identified, with 13 ending in A/U and one ending in C. These results are crucial for mining favorable genes related to photosynthesis and investigating the evolution of wild rice species. Overall, this study provides valuable information on the genomic composition and genetics of three Yunnan wild rice species.